HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN DAN PERSALINAN DAN RENCANA PENOLONG PERSALINAN DI WILAYAH KERJA PUSKESMAS KEBUMEN I - Ratna Dwi Listiyaningsih; Herniyatun -; Eni Indrayani (Jurnal Ilmiah Kesehatan Keperawatan, 2012)
Knowledge deficit of pregnant women and their families about the danger signs of pregnancy, childbirth, and postpartum needs to be improved to reduce MMR (Mothers’ Morbidity Rate) and IMR (Infant Mortality Rate). One of the effective ways to reduce maternal and infant mortality is to bring skilled birth attendant. This study aimed to determine the correlation between the knowledge of pregnant women about the danger signs in pregnancy and labor with the plan of choosing labor attendant in the region of Kebumen I Community Health Center. This study used a descriptive correlative research design. The populations in this study were pregnant women in the region of Kebumen I Community Health Center. 124 respondents were taken as the samples. The results indicated that 75 respondents (60.5%) had good knowledge about the danger signs of pregnancy and 71 respondents (57.3%) had good knowledge about the danger signs of labor and 4 respondents (3.2%) had plan to have midwife and obstetrician as their labor attendants. There is a correlation between the knowledge of pregnant women about the danger signs in pregnancy and labor with the plan of choosing labor attendant in the region of Kebumen I Community Health Center using a confidence level of 95 percent of earned value of p = 0.027. Keywords: knowledge, pregnant women, the danger signs in pregnancy and labor labor attendant